2020
DOI: 10.1007/s40122-020-00157-5
|View full text |Cite
|
Sign up to set email alerts
|

Injection Techniques for Common Chronic Pain Conditions of the Foot: A Comprehensive Review

Abstract: Purpose of Review: This is a comprehensive literature review of the available evidence and techniques of foot injections for chronic pain conditions. It briefly describes common foot chronic pain syndromes and then reviews available injection techniques for each of these syndromes, weighing the available evidence and comparing the available approaches. Recent Findings: Foot and ankle pain affects 20% of the population over 50 and significantly impairs mobility and ability to participate in activities of daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 100 publications
1
17
0
1
Order By: Relevance
“…Several studies have indicated little to no pain relief in patients treated for tendinosis pathologies or rotator cuff tears (143) (144). In contrast, several other studies indicated that PRP reduced or even eliminated pain in patients suffering from tendinosis, OA, plantar fasciitis, and other foot and ankle disorders (145) (146). The final platelet concentration and the biocellular composition have been identified as key PRP characteristics that contributed to the consistent analgesic effects observed after PRP applications.…”
Section: Prp Analgesic Effectsmentioning
confidence: 99%
“…Several studies have indicated little to no pain relief in patients treated for tendinosis pathologies or rotator cuff tears (143) (144). In contrast, several other studies indicated that PRP reduced or even eliminated pain in patients suffering from tendinosis, OA, plantar fasciitis, and other foot and ankle disorders (145) (146). The final platelet concentration and the biocellular composition have been identified as key PRP characteristics that contributed to the consistent analgesic effects observed after PRP applications.…”
Section: Prp Analgesic Effectsmentioning
confidence: 99%
“…The TN terminates by dividing into medial and lateral plantar nerves (MPN/LPN) (see Fig. 2) (Soneji & Peng, 2016;Urits et al, 2020).…”
Section: Anatomymentioning
confidence: 99%
“…TTS may have multiple causes such as thickening of the flexor retinaculum, bone compression or intra-tunnel pathologies (such as flexor tenosynovitis), cysts and other soft tissue masses, accessory muscles or vein-related pathology (Fantino et al, 2020). Diagnosis is based on the clinical history and physical examination findings, including a positive Tinel sign at the tarsal tunnel, which can be confirmed with magnetic resonance imaging (MRI) to identify space occupying lesions (SOLs) and nerve conduction studies (Urits et al, 2020). Ahmad et al (2012) and McSweeney and Cichero (2015) provide useful narrative overviews of the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Thema der lokalen Schmerztherapie umfasst sicher mehr als hier im Rahmen dieses Artikels darstellbar. Es sei auf entsprechende Übersichtsarbeiten zu diesem Thema verwiesen [97][98][99][100][101].…”
Section: Lokale Schmerztherapieunclassified